2021
DOI: 10.1002/adhm.202101867
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Delivery from Granular Hydrogels

Abstract: Nucleic acid delivery has applications ranging from tissue engineering to vaccine development to infectious disease. Cationic polymer condensed nucleic acids are used with surface‐coated porous scaffolds and are able to promote long‐term gene expression. However, due to surface loading of the scaffold, there is a limit to the amount of nucleic acid that can be loaded, resulting in decreasing expression rate over time. In addition, surface‐coated scaffolds are generally non‐injectable. Here, it is demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 75 publications
(110 reference statements)
0
37
0
Order By: Relevance
“…For therapeutic delivery and 3D printing, hydrogels should possess good injectability, shear-thinning, and self-healing ability. Jammed granular hydrogels have demonstrated their potential uses as injectable therapeutic carriers and 3D-printing inks. ,, However, the low stability of granular hydrogels without interparticle cross-linking in a physiological environment limits their broader use. Granular microgels cross-linked by dynamic hydrazone bonds allowed it to be deformable and shear-thinning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For therapeutic delivery and 3D printing, hydrogels should possess good injectability, shear-thinning, and self-healing ability. Jammed granular hydrogels have demonstrated their potential uses as injectable therapeutic carriers and 3D-printing inks. ,, However, the low stability of granular hydrogels without interparticle cross-linking in a physiological environment limits their broader use. Granular microgels cross-linked by dynamic hydrazone bonds allowed it to be deformable and shear-thinning.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, CS was selected due to its ability to absorb charged proteins and growth factors, such as transforming growth factor β (TGF-β) and platelet-derived growth factor-BB (PDGF-BB) . The ability of the granular hydrogels to load and release biomolecules in vitro was investigated . The study showed the development of a tailored granular hydrogel that can be easily administered without the need for post-injection cross-linking.…”
Section: Introductionmentioning
confidence: 99%
“…Granular hydrogels, also known as densely packed or jammed hydrogel microparticles, have recently contributed significantly to advances in material chemistry and tissue engineering because of their unique properties including inherent porosity, shear‐thinning, self‐healing, modular nature, and so on 1,4,25 . Inspired by this, we reported a novel BDDE‐crosslinked HA granular hydrogel (n‐HA) for the first time as a promising therapeutic alternative to current commercial HA products for OA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a serious chronic degenerative disease characterized by articular cartilage loss, synovitis, subchondral bone sclerosis, and osteophyte, which is the main cause of joint pain and disability 1–6 . The progression of OA may ultimately lead to keen arthroplasty surgery to restore joint function 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels are three-dimensional cross-linked hydrophilic polymeric networks with the ability to hold large amounts of water, formed by physical and/or chemical cross-linking (21)(22)(23)(24). Hydrogels used for controlled release of nucleic acids, entrapped either as conjugates or as polyplex (polymer-nucleic acid complex) particles, have been studied in several studies but are limited by low loading density because of their aggregation and instability during encapsulation by gelation (25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%